2017
DOI: 10.1146/annurev-orgpsych-032516-113316
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience in Organizational Behavior

Abstract: In this review, we consider the advent of neuroscience in management and organizational research. We organize our review around two general themes pertaining to how areas of the brain may be relevant to management and organizational behavior. First, intrinsic, at-rest activity in the brain provides trait-like information that can be used to better understand individuals in terms of cognition, emotions, and behaviors. Second, reflexive activity involves an understanding of the brain in terms of its state-like r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 78 publications
0
44
0
2
Order By: Relevance
“…Lian et al (2017) considered how control capacity could be characterized in both state and trait terms, and specifically suggested the potential relevance of neuroanatomical differences with regard to the latter. Such differences align with what is known as the relatively enduring, intrinsic structure of the brain (Waldman, Ward, & Becker, 2017b). The assessment of individual differences pertaining to intrinsic brain structures is becoming increasingly recognized for its importance in predicting cognition, emotions, and behavior (Lindquist, Wager, Kober, Bliss-Moreau, & Barrett, 2012;Raichle & Snyder, 2007;Waldman et al, 2017b), including the assessment of executive control (e.g., Hofmann et al, 2010;Mazoyer et al, 2001).…”
Section: Executive Control and Abusive Supervisionmentioning
confidence: 80%
See 1 more Smart Citation
“…Lian et al (2017) considered how control capacity could be characterized in both state and trait terms, and specifically suggested the potential relevance of neuroanatomical differences with regard to the latter. Such differences align with what is known as the relatively enduring, intrinsic structure of the brain (Waldman, Ward, & Becker, 2017b). The assessment of individual differences pertaining to intrinsic brain structures is becoming increasingly recognized for its importance in predicting cognition, emotions, and behavior (Lindquist, Wager, Kober, Bliss-Moreau, & Barrett, 2012;Raichle & Snyder, 2007;Waldman et al, 2017b), including the assessment of executive control (e.g., Hofmann et al, 2010;Mazoyer et al, 2001).…”
Section: Executive Control and Abusive Supervisionmentioning
confidence: 80%
“…Such differences align with what is known as the relatively enduring, intrinsic structure of the brain (Waldman, Ward, & Becker, 2017b). The assessment of individual differences pertaining to intrinsic brain structures is becoming increasingly recognized for its importance in predicting cognition, emotions, and behavior (Lindquist, Wager, Kober, Bliss-Moreau, & Barrett, 2012;Raichle & Snyder, 2007;Waldman et al, 2017b), including the assessment of executive control (e.g., Hofmann et al, 2010;Mazoyer et al, 2001). The intrinsic brain reflects the stable and relatively permanent capacity of the individual in terms of mental functioning and behavioral potential.…”
Section: Executive Control and Abusive Supervisionmentioning
confidence: 84%
“…In any case, Peterson et al (2008) does not report any data, or link to any external dataset or supplementary information that can be used to evaluate the content of what is reported. This is problematic because this study has been repeatedly and explicitly cited as an example of high-quality empirical work in almost every review of the literature since its publication (e.g., Butler, O'Broin, Lee, & Senior, 2015;Waldman et al, 2017;. Because this study is so consistently raised to the status of a high-quality empirical study, Peterson et al (2008) must be evaluated according to the same standards as any other empirical publication.…”
Section: Post-publication Peer Reviewmentioning
confidence: 99%
“…Waldman et al (2013a) represents a single dataset that has been reported through multiple venues, where each venue provides a different level of detail regarding methods, analytic strategy, and results. Our critical review is therefore guided by the ini-tial work that was published through conference proceedings (Waldman et al, 2013a), the unpublished preprint available on the ResearchGate repository (Waldman et al, 2013b), and the published textbook chapter within which it is discussed at length (Waldman, Stikic, Wang, Korszen, & Berka, 2015). In this commentary we focus on the neuroscience component of the study and examine the claim that the EEG measure represented a valid index of organizational engagement.…”
Section: Waldman Et Al (2013a) Emergent Leadership and Team Engagemmentioning
confidence: 99%
See 1 more Smart Citation